Paclobutrazol for height control of petunias - Francescangeli, Nora; Zagabria, Ana (Instituto de Investigaciones Agropecuarias (INIA. Chile), 2019)
The effects of paclobutrazol on the height of Petunia × hybrida hort. ex E. Vilm. were studied. An experiment on 'Bravo F1' was performed at the National Institute for Agricultural Technology (INTA), San Pedro Agricultural Experimental Station (33º4’ S, 59º4’ W), Buenos Aires Province, Argentina, in the spring of 2006. Treatments consisted of three colours of flower (white, red and blue), four concentrations of paclobutrazol by irrigation (0, 5, 10 and 15 mg L-1 and three application times (at 10-12, 18-20 and 26-28 leaves). Height at 45 d after transplanting (dat), days to appearance, opening and fall of the first flower and number of flowers at 21 and 45 dat were registered. Differences between control plants due to flower colour were detected, and would indicate the need of a differential management: at 45 dat, the height of red-flowered plants (22.3 cm) was less (P < 0.05) than white- (25.2 cm) or blue-flowered plants (26.4 cm). Paclobutrazol allowed for reducing height in all treated plants. The minimal concentrations that induced maximum effects were: 10 mg L-1 for blue-flowered plants (56% shortening), 5 mg L-1 for white-flowered plants (40% shortening) and 10 mg L-1 for red-flowered plants (38% shortening). In order to minimize the slightly deleterious effects detected in the number of blue and red flowers at 45 dat, early application would be advisable (10-12 leaves) for blue-flowered plants and more delayed (at 18-20 leaves) for red-flowered plants.